Efektivitas Program Keluarga Harapan (PKH) dan Dampaknya Terhadap Religiositas Masyarakat Penerima Bantuan di Kabupaten Solok - Awaludini Marifatullah; Syamsurizal Syamsurizal; Abdul Rahim. A; Novi Yanti; Fransiska Riana (Hikmah, 2021)
Program Keluarga Harapan (PKH) is a government program that aims to improve the welfare of the community. However, the facts on the ground show that many people do not use it properly, so this has an impact on dishonesty which has an effect on the religiosity of the beneficiaries. Therefore, this study aims to measure the effectiveness of the Family Hope Program and review the impact of religiosity. This type of research is field research, with quantitative methods. The data in this study comes from primary data in the form of assistance data from the Family Hope Program in Solok district and secondary data from data from the Central Statistics Agency and the Ministry of Social Affairs. Two models of analytical tools used are simple mathematics to measure the level of effectiveness and product moment correlation from Pearson. The results of the study prove that the impact of the Family Hope Program assistance in poverty alleviation in Solok Regency with a predicate of 81% and is in the very effective category. However, the output indicators on the items of responsibility in the religious sector are still less effective because awareness for increasing faith is still lacking.